Supervising from the Periphery: Educational Leader in Ensuring Instructional Quality for Geographically Isolated and Disadvantaged Areas - Dugasan, Nadzmin; Pajiji, Jocelyn; Onaid, Annie Rose; Abdurasid, Rasul (International Journal of Sustainability and Advanced Integrated Research, 2026)
This phenomenological study explored the lived experience of an educational commissioner in supervising instructional quality in geographically isolated and disadvantaged areas within the Bangsamoro Autonomous Region in Muslim Mindanao. Anchored in clinical supervision and adaptive leadership, the study examined how instructional supervision is sustained when conventional monitoring systems, digital reporting tools, standardized performance indicators, and regular school visits are constrained by distance, weak infrastructure, unstable communication, limited resources, and local cultural conditions. Data were gathered through a semi-structured interview with one educational commissioner who served as the key informant, and the responses were analyzed using thematic analysis. The findings revealed that effective supervision in GIDAs was sustained through community-based monitoring, remote communication, flexible reporting tools, teacher-centered dialogue, adaptive scheduling, commitment to care, empathy, mentorship, trust-building, contextualized RPMS implementation, local indicators and rubrics, collaborative evaluation, policy adaptation through dialogue, and cultural responsiveness. The study further showed that supervision in remote schools extends beyond compliance and formal evaluation; it requires relational trust, moral responsibility, community participation, and context-sensitive leadership. The main conclusion is that instructional quality can be maintained in marginalized educational settings when supervision is humane, adaptive, collaborative, and culturally responsive. The study recommends strengthening localized supervision frameworks that allow educational leaders to adapt evaluation tools, reporting systems, schedules, and supervisory practices according to actual field conditions. The study supports SDG 4 on Quality Education, SDG 10 on Reduced Inequalities, SDG 16 on Strong Institutions, and SDG 17 on Partnerships for the Goals. Its sustainability impact lies in advancing educational, governance, institutional, cultural, and community sustainability in remote and underserved schools.
Keywords: Adaptive Leadership; Community-Based Monitoring; Cultural Responsiveness; Instructional Supervision; Relational Trust; Teacher Support